2015
DOI: 10.1017/s1474747215000177
|View full text |Cite
|
Sign up to set email alerts
|

Financial literacy, trust and retirement planning

Abstract: We study the complex relationship between financial literacy, retirement planning and trust in financial institutions, using data from the 2010 Bank of Italy Survey on Household Income and Wealth. The impact of financial literacy on retirement planning is a well-established issue in the existing empirical literature; our main contribution is proving that financial knowledge not only impacts retirement planning, but also the decisions of entering a private pension scheme (or devoting the severance pay to a priv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 30 publications
5
31
0
2
Order By: Relevance
“…Unlike previous studies on the relationship between self-control and retirement savings, our analyses incorporate a variable capturing the individual's level of financial literacy. In this respect, a non-negligible number of empirical studies have found strong evidence of the effect of financial literacy on this financial behaviour (e.g., Ricci & Caratelli, 2017), as also confirmed by our empirical evidence. Moreover, even controlling for the individuals' financial literacy (Lusardi, 2008), the self-control variable remains statistically significant and positively related to holding retirement assets.…”
Section: Multivariate Analysissupporting
confidence: 88%
See 1 more Smart Citation
“…Unlike previous studies on the relationship between self-control and retirement savings, our analyses incorporate a variable capturing the individual's level of financial literacy. In this respect, a non-negligible number of empirical studies have found strong evidence of the effect of financial literacy on this financial behaviour (e.g., Ricci & Caratelli, 2017), as also confirmed by our empirical evidence. Moreover, even controlling for the individuals' financial literacy (Lusardi, 2008), the self-control variable remains statistically significant and positively related to holding retirement assets.…”
Section: Multivariate Analysissupporting
confidence: 88%
“…Moreover, the three above-mentioned papers use one or two-item scales to measure self-control, which could by a rather limited approach to capture financial self-control. Secondly, none of the three studies have considered financial literacy as a correlate, in spite of numerous studies that have proved that the individual's financial literacy affects the decision to save for retirement (Lusardi & Mitchell, 2011;Ricci & Caratelli, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This can be interpreted that those who have acquired a higher level of basic financial literacy have a propensity for making an investment choice for retirement. This finding is confirmed and in a similar trend, in comparison with prior studies conducted by Fornero and Monticone (2011) and Ricci and Caratelli (2017). Similarly, those who have gained greater pension knowledge have a propensity to exercise retirement investment choice.…”
Section: Regression Analysissupporting
confidence: 87%
“…Finally, following Ricci and Caratelli (), we consider the number of inhabitants in the municipality of residence, assuming that larger municipalities provide easier access to banking services, information and communication technologies, and education; for these reasons, municipality of residence may have a positive effect on individual financial literacy.…”
Section: Sample and Methodologymentioning
confidence: 99%
“…We insert two dummy variables: the first is equal to 1 when the respondent is employed, 0 otherwise; the second dummy variable is equal to 1 when the respondent is not employed but is seeking a job, 0 otherwise. 3 Finally, following Ricci and Caratelli (2015), we consider the number of inhabitants in the municipality of residence, assuming that larger municipalities provide easier access to banking services, information and communication technologies, and education; for these reasons, municipality of residence may have a positive effect on individual financial literacy.…”
Section: Explanatory Variables At Respondent Levelmentioning
confidence: 99%